[tex]6 \times | \frac{2}{3} - \frac{3}{4} | - | \frac{1}{3} - \frac{1}{2} | + \frac{2}{3} [/tex]
[tex] = 6 \times | \frac{8}{12} - \frac{9}{12} | - | \frac{2}{6} - \frac{3}{6} | + \frac{2}{3} [/tex]
[tex] = 6 \times | \frac{8 - 9}{12} | - | \frac{2 - 3}{6} | + \frac{2}{3} [/tex]
[tex] = 6 \times | - \frac{1}{12} | - | - \frac{1}{6} | + \frac{2}{3} [/tex]
[tex] = 6 \times \frac{1}{12} - \frac{1}{6} + \frac{2}{3} [/tex]
[tex] = \frac{6 \times 1}{12} - \frac{1}{6} + \frac{2}{3} [/tex]
[tex] = \frac{6}{12} - \frac{1}{ 6} + \frac{2}{3} [/tex]
[tex] = \frac{1}{2} - \frac{1}{6} + \frac{2}{3} [/tex]
[tex] = \frac{3}{6} - \frac{1}{6}+\frac{4}{6} [/tex]
[tex] = \frac{3-1+4}{6} [/tex]
[tex]=\frac{6}{6}[/tex]
[tex]=1[/tex]